THE EFFECT OF USING PICTURE SEQUENCES ON STUDENTS' NARRATIVE WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 4 SATU ATAP KUALA - DARMAWATI DARMAWATI; NURMALA SARI (LP2MTBM MAKARIOZ, 2022)
The study deals with the using of picture sequences method on students' narrative writing achievement. The purpose of this research was to see how employing picture sequences affected eighth grade students at SMP 4 Negeri Satu Atap Kuala ability to create narratives. The population of this research were eighth grade students at SMP Negeri 4 Satu Atap Kuala on JL. PKS Blankahan, Kecamatan Kuala, Kabupaten Langkat, in the odd semester. With a total population of 88 students in the school year 2021/2022. The experimental group has 22 students, while the control group has 22 students. The class has a total of 44 students in it. As a sample, the researcher picked a random sample from an even number of students. An experimental design methods was used in this research. A pictures sequences from narrative writing is used to teach learning groups. The experimental group's data collection tools are pre-test, treatment, and post-test. Based on the researcher it was found the t-test was determined to be higher than the t-table (8.01>2.01) with (α = 0.05). As well as the degree of freedom (df) 42. Including the findings, the percentage of the effect of using picture sequences method was 81.9%, with the remaining 18.1% influenced by other factors. It implies that using picture sequences has a significant impact on the achievement of eighth grade narrative writing from SMP Negeri 4 Satu Atap Kuala.